Understanding the Role of the Antioxidant Drug Erdosteine and Its Active Metabolite on Staphylococcus aureus Methicillin Resistant Biofilm Formation - Cristina Cattò; Federica Villa; Francesca Cappitelli (MDPI AG, 2021)
Increasing numbers of researches have suggested that some drugs with reactive oxygen species (ROS)-mediated mechanisms of action modulate biofilm formation of some pathogenic strains. However, the full contribution of ROS to biofilm development is still an open question. In this paper, the correlations between the antioxidant drug Erdosteine (Er) and its active Metabolite I (Met I), ROS and biofilm development of two strains of methicillin resistant Staphylococcus aureus are presented. Experiments revealed that Er and Met I at 2 and 5 mg/L increased up to three orders of magnitude the number of biofilm-dwelling cells, while the content of ROS within the biofilms was reduced above the 87%, with a major effect of Met I in comparison to Er. Comparative proteomics showed that, 5 mg/L Met I modified the expression of 30% and 65% of total proteins in the two strains respectively. Some proteins involved in cell replication were upregulated, and a nitric oxide-based mechanism is assumed to modulate the biofilm development by changing quorum sensitive pathways. Additionally, several proteins involved in virulence were downregulated in the presence of Met I, suggesting that treated cells, despite being greater in number, might have lost part of their virulence.